2016
DOI: 10.1182/blood-2014-05-575704
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD123 in acute myeloid leukemia using a T-cell–directed dual-affinity retargeting platform

Abstract: Key Points• A novel CD33CD123DART agent induces T-cell-target-specific association, activation, and proliferation.• The CD33CD123 DART induces a dose-dependent killing of AML cell lines and primary AML blasts in vitro and in vivo.T-cell-directed killing of tumor cells using bispecific antibodies is a promising approach for the treatment of hematologic malignancies. Here we describe our preclinical work with a dual-affinity retargeting (DART) molecule generated from antibodies to CD3 and CD123, designed to redi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(111 citation statements)
references
References 28 publications
(34 reference statements)
0
103
0
2
Order By: Relevance
“…Subsequently this group further explored the therapeutic potential of the CD123/ DART. They studied the interaction between T cells, antibody and primary human AML targets and cell lines in vitro and in vivo in non-obese diabetic immune deficient (NSG) mice (18). They confirmed that the CD123 DART binds to both human CD3 and CD123 to mediate targeteffector cell association, T-cell activation, proliferation, and receptor diversification.…”
Section: Antibody Designmentioning
confidence: 89%
See 1 more Smart Citation
“…Subsequently this group further explored the therapeutic potential of the CD123/ DART. They studied the interaction between T cells, antibody and primary human AML targets and cell lines in vitro and in vivo in non-obese diabetic immune deficient (NSG) mice (18). They confirmed that the CD123 DART binds to both human CD3 and CD123 to mediate targeteffector cell association, T-cell activation, proliferation, and receptor diversification.…”
Section: Antibody Designmentioning
confidence: 89%
“…Recombinant technology is used to link the variable heavy and light domains of two antibodies as a single 55 kDa polypeptide chain. In clinical (12); (II) chimeric antigen receptor T cell using anti CD123 to target myeloid cells (13,14) (not yet in clinical trial); (III) single polypeptide chain bispecific engager antibodies (BiTE) recognizing CD3 and CD3 (15) or CD123 (16); (IV) double polypeptide chain dual affinity retargeting antibodies (DART) recognizing CD3 and CD123 (17,18). AML, acute myelogenous leukemia; VL, light chain; VH, heavy chain; CD3z, zeta chain of CD3; Co-stim, costimulatory molecules.…”
Section: Antibody Designmentioning
confidence: 99%
“…7,8 Our in vitro HSC/progenitor CFU assay suggests minimal impact on hematopoiesis by a CLL-1 TDB, whereas it is ambiguous for a CD123-directed molecule given the reports of marked impairment of human hematopoiesis by a CAR-T-CD123, but none with a CD123-DART. [18][19][20] Rather than using an antibody-fragmentbased format like the CD33 BiTE 21 or CD123 DART, 19 a fulllength IgG was used for improving PK and potentially lowering immunogenicity. We hypothesized that CD3 affinity would be a key driver of both efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include unconjugated monoclonal antibodies, T-cell engaging bispecific antibodies, immunotoxins, and chimeric antigen receptor (CAR)-modified T cells (36)(37)(38)(39)(40)(41). Although each of the modality has its own advantages, our study shows that SGN-CD123A is highly active against AML models regardless of cytogenetic profiles and MDR status, and can be effectively combined with quizartinib.…”
Section: Mdr Proteins (30mentioning
confidence: 86%